2016
DOI: 10.1038/srep32361
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of in vivo metabolic flows reveals accelerated utilization of glucose and lactate in penumbra of ischemic heart

Abstract: Acute ischemia produces dynamic changes in labile metabolites. To capture snapshots of such acute metabolic changes, we utilized focused microwave treatment to fix metabolic flow in vivo in hearts of mice 10 min after ligation of the left anterior descending artery. The left ventricle was subdivided into short-axis serial slices and the metabolites were analyzed by capillary electrophoresis mass spectrometry and matrix-assisted laser desorption/ionization imaging mass spectrometry. These techniques allowed us … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 28 publications
0
59
0
Order By: Relevance
“…This suggests the presence of oxidative conversion of NADH to NAD + by mitochondrial complex I activity (Figure b). These imaging results were also supported by a capillary electrophoresis (CE)‐electrospray ionization (ESI)‐mass spectrometry (MS) technique (Morikawa et al, ; Sugiura et al, ; Supporting Information Figure S7). Taken together, these results suggest that while comparable a BOLD signal response was evoked by optogenetic stimulation of either neurons or astrocytes, the respective BOLD signal fluctuations were accompanied by distinct metabolic flows.…”
Section: Resultsmentioning
confidence: 77%
“…This suggests the presence of oxidative conversion of NADH to NAD + by mitochondrial complex I activity (Figure b). These imaging results were also supported by a capillary electrophoresis (CE)‐electrospray ionization (ESI)‐mass spectrometry (MS) technique (Morikawa et al, ; Sugiura et al, ; Supporting Information Figure S7). Taken together, these results suggest that while comparable a BOLD signal response was evoked by optogenetic stimulation of either neurons or astrocytes, the respective BOLD signal fluctuations were accompanied by distinct metabolic flows.…”
Section: Resultsmentioning
confidence: 77%
“…Rodents, rats and mice mainly, are frequently used as model organisms for basic research on metabolism. Metabolic profiling was performed on rodent muscle , heart , liver , brain , intestinal and glioma tissue, arterial cells as well as on rodent serum/plasma , urine and feces . CE‐MS was furthermore used for research on the metabolism of microorganism , plants and mushroom .…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…They reported that the fusion of the datasets prior to MCR‐ALS analysis was more effective in identifying low abundant metabolites . A combination with imaging MALDI‐MS for non‐targeted metabolomics in different regions of ischemic hearts was able to discover a heterogeneity in carbohydrate metabolism 10 min after initiation .…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…The samples were deparaffinized and covered with 9AA matrix followed by MSI in negative ion mode. Alternatively, for the preservation of the chemical composition of a cardiac tissue sample, rapid thermal inactivation is reported to be beneficial [ 62 , 63 ]. With this technique, fast heating of the sample denatures the enzymes, reducing the degradation of molecular compounds without morphological changes.…”
Section: Metabolite Msi and Cardiovascular Diseasesmentioning
confidence: 99%
“…The most frequently used matrices for metabolites are 9AA and N-(1-naphthyl) ethylenediamine dihydrochloride (NEDC) [ 63 ]. For identification purposes, an instrument with high mass resolution and accurate mass capabilities is required, for instance, FT-ICR-MS or orbitrap FTMS.…”
Section: Metabolite Msi and Cardiovascular Diseasesmentioning
confidence: 99%